THE USE OF MOBILE APPLICATIONS FOR LANGUAGE LEARNING: A STUDY ON EFFECTIVENESS AND STUDENT PERCEPTIONS - Nyak Mustakim; Syafiq Amir; Rashid Rahman (Journal International Inspire Education Technology, 2026)
The integration of mobile applications in language learning has gained significant attention due to their potential to enhance educational experiences. While several studies have explored their effectiveness, the relationship between mobile app usage and language proficiency improvements remains unclear. This research aims to evaluate the effectiveness of mobile applications for language learning and to explore students’ perceptions of these tools. A mixed-methods approach was employed, combining quantitative assessments of language proficiency (pre- and post-test scores) and qualitative student feedback through perception questionnaires and interviews. The sample consisted of 200 undergraduate students from a university, with 100 students using mobile applications and 100 using traditional methods. The findings revealed that the experimental group showed significant improvements in language proficiency, particularly in vocabulary and grammar, compared to the control group. Moreover, students in the experimental group reported higher satisfaction and engagement levels. These results suggest that mobile applications can significantly enhance language learning outcomes while offering an engaging, flexible learning experience. The study contributes to the growing body of research on mobile learning by providing a comprehensive evaluation of both objective outcomes and subjective experiences. Further research is needed to explore long-term impacts and the effectiveness of specific app features on language acquisition.